Life-stage dependent histological characterization of liver HIF-1α expression in the Indonesian shortfin eel (Anguilla bicolor bicolor McClelland, 1884) - Nyan Hayu Widiastuti; Bambang Retnoaji (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2022)
The Indonesian shortfin eel (Anguilla bicolor bicolor McClelland, 1884) is catadromous fish. The developmental phase of the fish is influenced by the availability and type of feed, and dissolved oxygen levels (DO). Oxygen level fluctuations during migration from sea to fresh waters can cause hypoxia and trigger activation of the Hypoxia-inducible factor 1 alpha gene (HIF-1α). Therefore, undertanding HIF-1α expression is very important in understanding the life cycle and physiology of this organism. This study aimed to perform a histological comparison between the liver structure of eel in the elver eel phase to silver eel and compared the expression of HIF-1α in the liver. The eels were collected from Kulon Progo Regency, Segara Anakan in Cilacap, and Cangkringan in Sleman, respectively. The eel livers were prepared with standard paraffin method. The samples were stained with Hematoxylin-Eosin, Mallory Acid Fuchsin and Periodic Acid-Schiff Alcian Blue for histological observation. The HIF-1α protein expression was detected using immunohistochemistry. The results showed that the structure of liver elver, yellow, and silver eel shared similar tubular hepatocytes. Moreover, there was no significant differences in the parenchymal structure of liver of all stage of eel. Mucin levels were different in each life cycle phase. HIF-1α expression varied by eel phase, with the elver eel showing weak expression, yellow stage showing moderate expression, and silver eels displaying the highest levels of expression. We conclude that the highest expression of HIF-1α was found in the silver eel, which resides in freshwater environments and is found in freshwater while returning to the sea for reproduction.